2009
DOI: 10.1016/j.biopsych.2008.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Association and Projection White Matter Systems in Alcoholism Detected with Quantitative Fiber Tracking

Abstract: Background Excessive alcohol use can cause macrostructural tissue shrinkage with regional preference for frontal systems. The extent and locus of alcoholism’s effect on white matter microstructure is less known. Methods Quantitative fiber tracking derived from diffusion tensor imaging (DTI) assessed the integrity of samples of 11 major white matter bundles in 87 alcoholics (59 men, 28 women) and 88 healthy control subjects (42 men, 46 women). Fiber integrity was expressed as fractional anisotropy (FA) and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
180
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(210 citation statements)
references
References 79 publications
28
180
2
Order By: Relevance
“…Lastly, DTI measures were correlated with cannabis use measures in the cannabis user group only. All white matter integrity analyses included covariates of age, gender, education, IQ, alcohol and cigarette consumption since these variables have known associations with white matter integrity (Szeszko et al 2003;Lebel et al 2008;Pfefferbaum et al 2009;Hudkins et al 2012). Given the unequal tobacco use between groups, we conducted additional partial analysis of models to assess for confounding of tobacco use which is presented in the supplemental information.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, DTI measures were correlated with cannabis use measures in the cannabis user group only. All white matter integrity analyses included covariates of age, gender, education, IQ, alcohol and cigarette consumption since these variables have known associations with white matter integrity (Szeszko et al 2003;Lebel et al 2008;Pfefferbaum et al 2009;Hudkins et al 2012). Given the unequal tobacco use between groups, we conducted additional partial analysis of models to assess for confounding of tobacco use which is presented in the supplemental information.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative diffusion tensor imaging has shown that excessive alcohol abuse not only causes macrostructural tissue shrinkage, but also fibre microstructure compromise with white matter degradation in multiple different fibre systems including the corpus callosum [10,11].…”
Section: Mri and Ct Findingsmentioning
confidence: 99%
“…11 In connection with chronic alcohol consumption, many previous DTI studies have reported reduced FA in certain brain regions: for example, in the genu of the corpus callosum; the centrum semiovale 12 ; and the frontal and superior sites, such as frontal forceps, internal and external capsules, and fornix. 13 DTI has revealed evidence for microstructral disruption of white matter in alcoholic men and women, even in regions appearing normal on conventional volume imaging.…”
mentioning
confidence: 99%